2017
DOI: 10.3847/1538-4357/aa9af0
|View full text |Cite
|
Sign up to set email alerts
|

On a Small-scale EUV Wave: The Driving Mechanism and the Associated Oscillating Filament

Abstract: We present observations of a small-scale Extreme-ultraviolet (EUV) wave that was associated with a mini-filament eruption and a GOES B1.9 micro-flare in the quiet Sun region. The initiation of the event was due to the photospheric magnetic emergence and cancellation in the eruption source region, which first caused the ejection of a small plasma ejecta, then the ejecta impacted on a nearby mini-filament and thereby led to the filament's eruption and the associated flare. During the filament eruption, an EUV wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 123 publications
2
43
0
2
Order By: Relevance
“…In recent years, more and more observational studies based on high resolution observations suggested that EUV waves should be CME driven fast-mode magnetosonic waves or shocks. This scenario has been confirmed by many observations and theoretical studies of the separation process between CMEs and waves (e.g., Long et al 2008;Gopalswamy et al 2009;Olmedo et al 2012;Yang et al 2013;Shen et al 2013bShen et al , 2017b. In addition, EUV waves can also be driven by sudden loop expansions caused by external disturbances (Shen et al 2018d) and coronal jets (Shen et al 2018a).…”
Section: Introductionmentioning
confidence: 71%
“…In recent years, more and more observational studies based on high resolution observations suggested that EUV waves should be CME driven fast-mode magnetosonic waves or shocks. This scenario has been confirmed by many observations and theoretical studies of the separation process between CMEs and waves (e.g., Long et al 2008;Gopalswamy et al 2009;Olmedo et al 2012;Yang et al 2013;Shen et al 2013bShen et al , 2017b. In addition, EUV waves can also be driven by sudden loop expansions caused by external disturbances (Shen et al 2018d) and coronal jets (Shen et al 2018a).…”
Section: Introductionmentioning
confidence: 71%
“…如果侧向和径向膨胀加速度都足 够快, 通常会形成圆顶状的EUV波 [47] ; 如果仅侧向膨胀 加速度足够快, 则在泡状结构侧向前方形成沿日面传 播的EUV波. 目前, 一些观测和理论研究倾向支持早期 的EUV波是由CME的侧向膨胀激发的 [43,48,52,84,89,90] . EUV波还有其他的一些激发方式, 包括小尺度喷 射现象、冕环膨胀以及爆发暗条中的丝状螺旋结构周 期性解缠等.…”
Section: Euv波的形成unclassified
“…如果是前者, 那么次级日冕暗化现象便更支持 [110,111] . 后来又发现, 在没有莫尔顿波的情况 下, EUV波也会导致暗条发生横向振荡 [44,45,90,112,113] . 当 日面上有多个暗条时, 因EUV波到达不同暗条需要的时 间不同, 暗条将按离爆发源区距离远近依次发生振荡运 动 [20,112] .…”
Section: 等现象充分展现了它波动性质的一面unclassified
“…Longitudinal oscillations can be triggered by microflares (Jing et al 2003;Vršnak et al 2007;Zhang et al 2012Zhang et al , 2017a, flares (Li & Zhang 2012;Zhang et al 2020b), coronal jets (Luna et al 2014), shock waves (Shen et al 2014), and failed filament eruptions (Mazumder et al 2020). Transverse prominence oscillations are often excited by Moreton waves and/or EUV waves from a remote site of eruption at speeds of ∼1000 km s −1 (e.g., Eto et al 2002;Gilbert et al 2008;Hershaw et al 2011;Asai et al 2012;Dai et al 2012;Gosain & Foullon 2012;Liu et al 2012;Shen et al 2017;Zhang & Ji 2018). Sometimes, they are triggered by magnetic reconnection as a result of magnetic flux emergence (Isobe & Tripathi 2006;Chen et al 2008).…”
Section: Introductionmentioning
confidence: 99%